Posterior Reversible Encephalopathy Syndrome, Part 2: Controversies Surrounding Pathophysiology of Vasogenic Edema - Bartynski, W.S. (AJNR Am J Neuroradiol, 2008)
SUMMARY: Posterior reversible encephalopathy syndrome (PRES) is a neurotoxic state accompanied by a unique brain imaging pattern typically associated with a number of complex clinical conditions including: preeclampsia/eclampsia, allogeneic bone marrow transplantation, solid organ transplantation, autoimmune diseases and high dose cancer chemotherapy. The mechanism behind the developing vasogenic edema and CT or MR imaging appearance of PRES is not known. Two theories have historically been proposed: 1) Severe hypertension leads to failed auto-regulation, subsequent hyperperfusion, with endothelial injury/vasogenic edema and; 2) vasoconstriction and hypoperfusion leads to brain ischemia and subsequent vasogenic edema. The strengths/weaknesses of these hypotheses are reviewed in a translational fashion including supporting evidence and current available imaging/clinical data related to the conditions that develop PRES. While the hypertension/hyperperfusion theory has been most popular, the conditions associated with PRES have a similar immune challenge present and develop a similar state of T-cell/endothelial cell activation that may be the basis of leukocyte trafficking and systemic/cerebral vasoconstriction. These systemic features along with current vascular and perfusion imaging features in PRES appear to render strong support for the older theory of vasoconstriction coupled with hypoperfusion as the mechanism.